The Sardinian Bitter Honey: From Ancient Healing Use to Recent Findings - Ignazio Floris; Michelina Pusceddu; Alberto Satta (MDPI AG, 2021)
Sardinian bitter honey, obtained from the autumnal flowering of the strawberry tree (Arbutus unedo L.), has an old fame and tradition in popular use, especially as a medicine. Its knowledge dates back over 2000 years, starting from the Greeks and Romans to the present day. There are many literary references from illustrious personalities of the past such as Cicero, Horace, Virgil, and Dioscorides, until recent times, associated with the peculiar anomaly of its taste, which lends itself to literary and poetic metaphors. The curiosity of its bitter taste is also what led to the first studies starting in the late 1800s, aimed to reveal its origin. Other studies on its botanical source and characteristics have been carried out over time, up to the most recent investigations, which have confirmed its potential for use in the medical field, thanks to its antioxidant, antiradical, and cancer-preventing properties. These benefits have been associated with its phenolic component and in particular with the prevailing phenolic acid (homogentisic acid). Later, other strawberry tree honeys from the Mediterranean area have also shown the same properties. However, Sardinian bitter honey maintains its geographical and historical identity, which is recognized by other Mediterranean cultures.